The crystal structure of 2-(2′-carboxybenzyl)benzoic acid, C15H12O5 - Xi-Hai Yan; Bo Zhao; Peng-Cheng Fan; Xi-Shi Tai (Zeitschrift für Kristallographie - New Crystal Structures)
C15H12O5, monoclinic, P21/c (no. 14), a = 16.1399(4) Å, b = 19.2950(5) Å, c = 8.2567(2) Å, β = 97.078(1)°, V = 2551.70(11) Å3, Z = 8, R gt(F) = 0.0440, wRref (F 2) = 0.1326, T = 299.15 K.